Applying Collaborative Ranking Tasks to Improve Students’ Concept Mastery and Generic Science Skills (Jurnal Pendidikan IPA Indonesia, 2018)
The lack of students concept mastery and generic science skills underlying this research. The purpose of this research was to improve the students’ concept mastery and generic science skill by applying the collaborative ranking-task model in Earth and Space Science learning. This type of research was a classroom action research, conducted in two cycles. The data were collected by observation technique, test, and questionnaire. The study was conducted on physics students amounted to 25 people (10 male and 15 female). The success of the study was determined by the grade point average which should be at least 70. The obtained data were analyzed descriptively. The results showed that there was an increase in the students’ concept mastery starting from cycle 1 to cycle 2 ( x1= 50, s1 = 11.4 in the ‘deficient’ category; and x2= 64, s2 = 8.3 in the ‘sufficient’ category). The generic science skills were numerically increased from cycle 1 to cycle 2 (x1= 58.4, s1 = 13.3; x2= 62.8, s2 =10.2; in the ‘moderate’category). The developed indicators of generic science skills included indirect observation, logic inference, and concept building. The mean score of student response was x = 58.6; s = 6.7 which was in the positive category.